2003
DOI: 10.1046/j.1439-0442.2003.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Lactoferrin Receptor in Bovine Intestine: Higher Binding Activity to the Epithelium Overlying Peyer's Patches

Abstract: Several lines of evidence have recently demonstrated the occurrence of specific lactoferrin (Lf) receptors in different cells. We report here, for the first time, the characteristics of binding, and distribution of Lf receptors in the bovine intestinal tract with special emphasis on the epithelium overlying Peyer's patches (EOPP). Brush-border membrane vesicles (BBMV) were prepared from the mucosa of duodenum, jejunum, ileum, colon, EOPP in jejunum and EOPP in ileum. Receptor binding assays were carried out us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…Macromolecules are transported from the gut to the systemic circulation either by specific receptor-mediated transcytosis or nonspecific transcytosis [29]. Nevertheless, IgG is not absorbed after the "Gut closure" in the intestines, but Lf-R are present in the intestines of different species, such as mice [18], piglets [13], monkeys [5], humans [20] and cows [34]. Together these studies suggest that Lf absorption in the gut involves receptor-mediated transcytosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macromolecules are transported from the gut to the systemic circulation either by specific receptor-mediated transcytosis or nonspecific transcytosis [29]. Nevertheless, IgG is not absorbed after the "Gut closure" in the intestines, but Lf-R are present in the intestines of different species, such as mice [18], piglets [13], monkeys [5], humans [20] and cows [34]. Together these studies suggest that Lf absorption in the gut involves receptor-mediated transcytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Iodination of Lf: Labeling of Lf with 125 I was performed in the presence of iodogen as a catalyst, by the method of Fraker and Speck [12] and described by Talukder et al [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lactoferrin receptor is expressed in many mammalian tissues, including intestine, heart, spleen, liver, monocytes, lymphocytes, platelets, and salivary glands (27 -30). The lactoferrin receptors found in the intestinal epithelium overlying peyers patches have the highest specific binding capability when compared with lactoferrin receptors at other sites (30). The murine lactoferrin receptor has 87% homology with the human receptor and shows binding specific for human, mouse, and bovine lactoferrin (28,31,32).…”
mentioning
confidence: 99%
“…As well, orally administered LF was reported to be absorbed into systemic circulation not only in neonates [6,14], but also in weaned pigs [5] and young cattle [16]. Talukder et al [15] reported the detection of a specific LF-receptor in adult cow intestines, including the duodenum, jejunum, ileum, and colon, and Peyer's patches in the jejunum and ileum. Interestingly, the density of LFreceptor was higher in Peyer's patches than in other regions of the intestine.…”
mentioning
confidence: 99%